A new version of the Behaviour of Young Novice Drivers Scale (BYNDS). Insights from a randomised sample of 700 German young novice drivers. (September 2020) - Jannusch, Tim; Völler, Michaele; Murphy, Finbarr; Mullins, Martin
Highlights: The inclusion of sixteen new items creates a timely commensurate BYNDS. In particular, a broader picture of smartphone use is introduced. The paper presents an innovative translation process easy to adopt. Pitfalls for response errors are addressed, and semantics are improved. The questionnaire was applied to a representative German sample of young drivers. Abstract: In Germany, every year 66, 000 road crashes lead to death or injury of young novice drivers. This makes them twice as likely to be involved in, or cause, vehicle crashes compared to their older and more experienced counterparts. This study aims to address this societal issue by developing a better understanding of the German young driver problem. For this purpose, we created an updated, 55-item strong version of the Behaviour of Young Novice Drivers Scale (BYNDS), originally developed by Scott-Parker et al. in 2010. To make the new version of the BYNDS understandable for German young novice drivers, this research used a new method of translation in combination with extensive pre-testing. As a result, we identified possible threats for response errors such as retrospective formulated questions or double negations. Due the adjustment of the possible sources of error the presented version of the BYNDS is semantically and conceptually different from the original. However, due to the application of the updated version of the BYNDS in a robust sample of 700 participants, this paper presents the first reliable and validated tool to measure novices risky driving behaviour in Germany. Moreover, it offers an updated and extended version of the BYNDS that allows practitioners but also researchers to broaden their understanding of young driver risk.